SENAM KAKI MENINGKATKAN SENSASI SENSORIS DIABETISI DENGAN DIABETIC PERIPHERAL NEUROPATHY - I Wayan Sukawana (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2018)
Hipoxia on axon and myelin caused by microangiopathy can lead to Diabetic Peripheral Neuropathy in people with diabetes. The aim of this research is to know the effect of foot gymnastics on DPN in people with diabetes. The study was conducted by quasi-pre-post experiment without group control of 13 people with DPN. Average number of DPN points before foot exercises = 4.42 points and after exercises = 0.46 points from 20 checkpoints. After exercising legs every 2 days for 6 weeks, all (100%) of the respondents experienced an increase in sensory sensation and 83.3% of them were free of DPN. T-paired t-test results obtained t value = 3.80 with a significance value of 0.003, so it is concluded that foot gymnastics can increase sensory sensation in diabetic patients with DPN.